A Roadmap for Sustainable Silvopastoral System Restoration - Louhaichi, Mounir; Hassan, Sawsan; Ouled Belgacem, Azaiez (Krishi Publisher, 2023)
The research was presented in the International Conference on Feeding the Future through Sustainable Eco-friendly Innovations in Rangeland, Forages, and Animal Sciences in Bangalore, India. The study identified the primary challenges and provided a roadmap for restoring degraded silvopastoral systems in a semi-arid region. The study explored a state-owned silvopastoral site in a semi-arid Tunisia region, highlighting challenges such as the lack of effective collaboration among departments and stakeholders and the detrimental effect of prolonged livestock exclusion on the ecosystem. Interventions involved erosion mitigation, afforestation with native species, and promoting multi-stakeholder engagement and supportive policies. The study underscored the importance of collaborative strategies in revitalizing degraded ecosystems.